2006
DOI: 10.4049/jimmunol.176.8.4666
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Inducing Kinase Is Involved in the Activation of the CD28 Responsive Element through Phosphorylation of c-Rel and Regulation of Its Transactivating Activity

Abstract: Previous evidence suggested that NF-κB-inducing kinase (NIK) might regulate IL-2 synthesis. However, the molecular mechanism is not understood. In this study, we show that NIK is involved in CD3 plus CD28 activation of IL-2 transcription. Splenic T cells from aly/aly mice (that have a defective NIK protein) have a severe impairment in IL-2 and GM-CSF but not TNF secretion in response to CD3/CD28. This effect takes place at the transcriptional level as overexpression of alyNIK inhibits IL-2 promoter transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 58 publications
4
52
1
Order By: Relevance
“…IKK-and NIK-associated kinases have been shown to phosphorylate sites within residues 422-540 of REL in vitro (Lawrence et al, 2005;Harris et al, 2006;Sa´nchez-Valdepen˜as et al, 2006), and we show that both IKKa and IKKb can phosphorylate Ser525 of REL in vitro. However, Ser525 appears to be only one of multiple sites in the C-terminal, half of REL that can serve as in vitro phosphorylation sites for IKK, given that a fragment containing the entire C-terminal REL transactivation domain with the S525P mutation has only a slightly reduced ability to be phosphorylated by IKKa and IKKb in vitro (Figure 6b and e).…”
Section: Discussionmentioning
confidence: 53%
“…IKK-and NIK-associated kinases have been shown to phosphorylate sites within residues 422-540 of REL in vitro (Lawrence et al, 2005;Harris et al, 2006;Sa´nchez-Valdepen˜as et al, 2006), and we show that both IKKa and IKKb can phosphorylate Ser525 of REL in vitro. However, Ser525 appears to be only one of multiple sites in the C-terminal, half of REL that can serve as in vitro phosphorylation sites for IKK, given that a fragment containing the entire C-terminal REL transactivation domain with the S525P mutation has only a slightly reduced ability to be phosphorylated by IKKa and IKKb in vitro (Figure 6b and e).…”
Section: Discussionmentioning
confidence: 53%
“…c-Rel-mediated transactivation is stimulated by phosphorylation within its transactivation domain at Ser-471 by PKCz in response to TNF and possibly also by NIK (Martin and Fresno, 2000;Martin et al, 2001;Sa´nchez-Valdepen˜as et al, 2006) (Figure 3; Table 4). Other residues in the c-Rel transactivation domain are also phosphorylated (Martin and Fresno, 2000), and mutation of Ser-454 and Ser-460 has been shown to affect c-Rel function (Starczynowski et al, 2005).…”
Section: Acetylation Of Relamentioning
confidence: 99%
“…2 Several groups have previously shown that NIK has an important role in IL-2 production by T cells. 15,16 IL-2 enhances the expansion of T lymphocytes and is crucial for correct CD8 effector function. 42 NIK regulates the production of IL-17, 27 another cytokine with a role in GVHD.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…This may be related to the lower IL-2 concentration found in aly/aly mice and the poor ability to release IL-2 shown in this study and previously described. 16 T-cell apoptosis linked to T-cell activation is a process known as activation-induced cell death. 30,31 T lymphocytes are resistant to activation-induced cell death in the earliest period after activation.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation